Experimental study on the effect of saturation magnetization of hematite nanocatalyst for green ammonia production - Alqasem, B. (American Institute of Physics Inc., 2016)
Hematite nanocatalysts with different magnetic properties were synthesized by heating pure iron wires at temperatures (600°C and 700°C) with the presence of water vapor. The physical and chemical characteristics of the nanocatalysts were studied using analytical methods. From Field Emission Scanning Electron Microscopy (FESEM) results it was found that the morphology of the nanocatalyst was changed by changing the synthesis temperature. The nanowires were formed when the synthesis temperature was 600°C while at 700°C the shape changed to clusters. By using the Vibrating Sample Magnetometer (VSM) the results show that the magnetic properties of the nanocatalysts were changed by changing the synthesis temperature, the highest saturation magnetization value (168.8 emu/g) was obtained for the sample prepared at 600°C. The iron oxide nanocatalysts were used to synthesize ammonia at 0.5T external magnetic field. The highest yield of ammonia (18.23 mmol h-1gcat-1) was achieved by using α-Fe2O3 nanowires which have the highest saturation magnetization. © 2016 Author(s).